2022
DOI: 10.3390/brainsci12101344
|View full text |Cite
|
Sign up to set email alerts
|

The ALFF Alterations of Spontaneous Pelvic Pain in the Patients of Chronic Prostatitis/Chronic Pelvic Pain Syndrome Evaluated by fMRI

Abstract: Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is a challenging entity with complicated symptoms for treatment in the male crowd. Accumulating evidence revealed the dysfunction in the central system should be a critical factor for the pathogenesis and development in the CP/CPPS. Therefore, we recruited 20 patients of CP/CPPS and 20 healthy male volunteers, aged 20 to 50 years. Through resting-state functional magnetic resonance imaging (fMRI), we analyzed the mean amplitude of low-frequency fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…These non-invasive and objective methods of brain functional measurement have been proven to be invaluable in gaining a deeper understanding of pain sensitization mechanisms in patient populations and for exploring analgesic targets ( 20 ). Furthermore, research studies have revealed regional functional abnormalities [amplitude of low-frequency fluctuation and regional homogeneity ( 21 23 )], alterations in the pain modulation pathway [e.g., pain ascending/descending pathway ( 24 )], and network reorganizations [e.g., default mode network and saliency network ( 25 , 26 )], which were associated with pain hypersensitivity in various chronic pain conditions. While previous studies have identified brain neuropathological changes in chronic pain patients, the central mechanisms of pain are yet to be studied in depth in FS.…”
Section: Introductionmentioning
confidence: 99%
“…These non-invasive and objective methods of brain functional measurement have been proven to be invaluable in gaining a deeper understanding of pain sensitization mechanisms in patient populations and for exploring analgesic targets ( 20 ). Furthermore, research studies have revealed regional functional abnormalities [amplitude of low-frequency fluctuation and regional homogeneity ( 21 23 )], alterations in the pain modulation pathway [e.g., pain ascending/descending pathway ( 24 )], and network reorganizations [e.g., default mode network and saliency network ( 25 , 26 )], which were associated with pain hypersensitivity in various chronic pain conditions. While previous studies have identified brain neuropathological changes in chronic pain patients, the central mechanisms of pain are yet to be studied in depth in FS.…”
Section: Introductionmentioning
confidence: 99%
“…Among fMRI analysis methods, ALFF can directly reflect the magnitude of baseline changes in the brain blood oxygen level-dependent effect (BOLD) signal and indirectly indicate the intensity of local neuronal spontaneous activity in the brain. ALFF is considered to be one of the most common methods for observing changes in brain function at rest and is widely used in brain function studies of pain-related diseases (Zang, 2016;Du et al, 2018;Pan et al, 2018;Ge et al, 2022). Therefore, we used a data-driven ALFF analysis to explore differences in brain activity between patients with lumbar disc herniation chronic low back pain (LDHCP) and healthy controls (HCs).…”
Section: Introductionmentioning
confidence: 99%